Eve eaudiobook How the female body drove 200 million years of human evolution. - Bohannon, Cat (Books on Tape, 2023)
An ambitious, eye-opening, myth-busting, and groundbreaking history of the evolution of the female body, by a brilliant new researcher and writer Why do women live longer than men? Why do women have menopause? Why are women more likely to get Alzheimer’s? Why do girls score better at every academic subject than boys until puberty, when suddenly their scores plummet? And does the female brain really exist? In Eve, Cat Bohannon answers questions scientists should have been addressing for decades. With boundless curiosity and sharp wit, she covers the past 200 million years to explain the specific science behind the development of the female sex. Eve is not only a sweeping revision of human history, it’s an urgent and necessary corrective for a world that has focused primarily on the male body for far too long. Bohannon’s findings, including everything from the way C-sections in the industrialized world are rearranging women’s pelvic shape to the surprising similarities between pus and breast milk, will completely change what you think you know about evolution and why Homo sapiens have become such a successful and dominant species, from tool use to city building to the development of language. Picking up where Sapiens left off, Eve is a landmark book, offering a true paradigm shift in our thinking about what the female body is and why it matters. * This audiobook edition contains a downloadable PDF of illustrations that can be viewed on any MAC or PC device.